Self-steerable propulsion of disk-like micro-craft with dual off-center nanoengines - Hu, Liangxing (2020)
This paper reports a novel disk-like micro-craft with dual off-center nozzle nanoengines, consisting of three different metals: gold, nickel, and platinum. A bubble propulsion mechanism originating from momentum change induced by the detachment of oxygen bubbles is proposed to elaborate the self-steerable propulsion of the disk-like gold-nickel-platinum micro-craft. The as-proposed micro-craft is fabricated by a layer-by-layer deposition method based on the micro-electro-mechanical systems technology. Herein, the self-steerable propulsion of the fabricated micro-craft dispersed in deionized water with different hydrogen peroxide concentrations is characterized. As a consequence, the speed of the micro-craft is increased with the increment of hydrogen peroxide concentration. In addition, the micro-craft can always move forward linearly.